Theory of General Relativity: Historical Perspective - Yadav, Ranjit Prasad (Academic Voices: A Multidisciplinary Journal, 2015)
General relativity was developed by Albert Einstein near about 100 Years ago. This article attempt to give an outline about the brief history of general theory of relativity and to understand the background to the theory we have to look at how theories of gravitation developed. Before the advent of GR, Newton's law of gravitation had been accepted for more than two hundred years as a valid description of the gravitational force between masses i.e. gravity was the result of an attractive force between massive objects. General relativity has developed in to an essential tool in modern astrophysics. It provides the foundation for the understanding of black holes, regions of space where gravitational attraction is strong that not even light can escape and also a part of the big bang model of cosmology. DOI: http://dx.doi.org/10.3126/av.v4i0.12358 Academic Voices Vol.4 2014: 49-52